TINJAUAN YURIDIS PENEGAKAN HUKUM ILLEGAL FISHING DI NATUNA UTARA (Lex Jurnalica, 2023)
This study aims to elaborate the urgency and strategy of law enforcement of illegal fishing in North Natuna waters, Indonesia, in accordance with positive laws and regulations. Using juridical-normative research methods and descriptive-analytical approaches, this study examines Indonesia's position and importance in law enforcement in North Natuna. The results of the analysis in this study identify the economic potential in North Natuna as one of the potential sources in increasing state revenue from the maritime sector. North Natuna also has potential strategic value as a shipping lane and natural gas reserves. With its status as a conflict area due to China's Nine Dash Line claims and being the outermost area of the EEZ, North Natuna has a high vulnerability to illegal fishing. Thus, law enforcement becomes a fundamental aspect that is urgent and important to be optimized. Regulatory improvements, institutional reconstruction, and synergy of Indonesia's international relations with Southeast Asian countries need to be formulated to reduce the rate of illegal fishing and provide security guarantees for North Natuna's maritime resources.